Dietary Carbohydrates, their Chemical Properties (International Journal of Scientific Trends, 2024)
Food science is an applied branch of science that deals with the study of food production methods. The modern food industry receives dozens of products with their own amazing technologies, equipment and equipment. With the participation of these enterprises, grain, flour, cereals, compound feed, bread, pasta, confectionery, oil and fat, sugar, meat, dairy, canned products, alcohol, beer and other food products necessary for human consumption are produced.